Pengaruh Fasilitas dan Aksesibiltas Terhadap Kepuasan Pengunjung di Taman Menteng Bintaro Jaya, Tangerang Selatan - Oktavia, Reno Catelya Dira; Hidayat, Candra; Wicaksono, Haryo; Taviprawati, Ervina; Yasin, Andi Muhammad (Jurnal Ilmiah Pariwisata, 2025)
This study aims to analyze the influence of accessibility and facilities on visitor satisfaction at Menteng Park, Bintaro Jaya, South Tangerang. This study used a quantitative approach with a descriptive and explanatory research design. The study population was visitors to Menteng Park during the study period, with a sample of 200 respondents selected using a purposive sampling technique. Data were collected through a questionnaire survey measuring accessibility, facilities, and visitor satisfaction. Data analysis was conducted using multiple linear regression. The results showed that accessibility and facilities significantly influenced visitor satisfaction. Good accessibility, such as easy transportation and parking availability, contributed to visitor comfort, while adequate facilities, such as seating, play areas, and clean restrooms, increased visitor satisfaction. These two factors are interrelated and strengthen positive visitor experiences. Menteng Park management needs to continuously improve the quality of accessibility and facilities to enhance visitor satisfaction. This study recommends improving pedestrian paths, adding parking facilities, and providing more comfortable public spaces. Further research could explore the social and environmental factors that influence satisfaction and examine the relationship between accessibility, facilities, and visitor loyalty. Keywords: facilities, accessibility, visitor satisfaction